Integrating Pancasila Values into Ethnomathematics: A Project-Based Approach to Strengthening Problem-Solving Skills - Kamid, Kamid; Asrial, Asrial; Maison, Maison; Novferma, Novferma (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study investigated the integration of Pancasila values into ethnomathematics-based learning through a project-based learning approach to enhance students’ problem-solving skills. A quasi-experimental design with a pretest–posttest non-equivalent control group was conducted at SMAN 8 Muaro Jambi, involving 62 grade XI students. The instruments consisted of a mathematical problem-solving test, observation sheets, and rubrics for assessing Pancasila values during learning activities. Data were analyzed using paired and independent sample t-tests, normalized gain (N-Gain), and effect size. The findings revealed that the posttest mean score of the experimental class, taught by using the PjBL integrated with ethnomathematics contexts including weaving patterns and local architectuaral designs,was significantly higher than that of the control one (78.94 compared to 69.48). The N-gain of the experimental group (0.61) belonged to medium-high, while that of the control group was only 0.32. Cohen’s d for effect size was 0.82, which was classified as a large effect. Qualitative results also described that collaboration, tolerance, and responsibility in the experimental class were higher, which indicated the implementation of Pancasila values in project activities. The results of this study show that an integration of ethnomathematics and Pancasila values in PjBL can enhance the both student’s problem-solving skills and character.